Epistemologi Dan Metodologi Tafsir Dalam Tarjumān Al-Mustafīd Karya ‘Abd Al-Ra’ūf Al-Singkilī Sebagai Model Lokalisasi Intelektual Islam Nusantara - Enep Syamsudin; Suryaman; Zakaria, Aceng (Dirosah Islamiyah, 2026)
Tarjumān al-Mustafīd by ‘Abd al-Ra’ūf al-Singkilī is a monumental milestone in Islamic historiography, widely recognized as the first complete 30-chapter (juz) exegesis written in the Malay language using Jawi script in Southeast Asia. This library research, centered on textual analysis and intellectual history, aims to deconstruct al-Singkilī’s hermeneutical methodology and map the epistemological framework of 17th-century Nusantara exegesis by synthesizing contemporary academic literatures. The findings demonstrate that the cognitive structure of Tarjumān al-Mustafīd is anchored in the concept of "epistemic localization," which bridges classical Middle Eastern intellectual traditions with the practical needs of the local Malay community. Methodologically, al-Singkilī combined the tahlīlī method with an ijmālī interpretive focus, operationalized through the technique of tarjamah tafsīriyah. Epistemologically, while al-Singkilī anchored his scientific authority within classical Sunni-Orthodox commentaries, he consciously eliminated convoluted theological disputes (kalam) and dense grammatical (nahwu) debates to maintain social stability and counteract the local crisis of the heterodox Wujudiyah doctrine in Aceh. This study underscores that the originality of Tarjumān al-Mustafīd lies not in radical theoretical innovations but in its creative linguistic and pedagogical adaptation, successfully laying the foundation for moderate Islam (wasathiyah) in Southeast Asia.